Research advances on signaling pathways regulating the polarization of tumor-associated macrophages in lung cancer microenvironment - Li, Wenqiang; Yuan, Quan; Li, Mei; He, Xiaoyu; Shen, Chen; Luo, Yurui; Tai, Yunze; Li, Yi; Deng, Zhiping; Luo, Yao (Frontiers in Immunology, 2024)
Lung cancer (LC) is one of the most common cancer worldwide. Tumor-associated macrophages (TAMs) are important component of the tumor microenvironment (TME) and are closely related to the stages of tumor occurrence, development, and metastasis. Macrophages are plastic and can differentiate into different phenotypes and functions under the influence of different signaling pathways in TME. The classically activated (M1-like) and alternatively activated (M2-like) represent the two polarization states of macrophages. M1 macrophages exhibit anti-tumor functions, while M2 macrophages are considered to support tumor cell survival and metastasis. Macrophage polarization involves complex signaling pathways, and blocking or regulating these signaling pathways to enhance macrophages' antitumor effects has become a research hotspot in recent years. At the same time, there have been new discoveries regarding the modulation of TAMs towards an anti-tumor phenotype by synthetic and natural drug components. Nanotechnology can better achieve combination therapy and targeted delivery of drugs, maximizing the efficacy of the drugs while minimizing side effects. Up to now, nanomedicines targeting the delivery of various active substances for reprogramming TAMs have made significant progress. In this review, we primarily provided a comprehensive overview of the signaling crosstalk between TAMs and various cells in the LC microenvironment. Additionally, the latest advancements in novel drugs and nano-based drug delivery systems (NDDSs) that target macrophages were also reviewed. Finally, we discussed the prospects of macrophages as therapeutic targets and the barriers to clinical translation.